2016
DOI: 10.21037/acs.2016.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Improved cardiac function and exercise capacity following correction of pectus excavatum: a review of current literature

Abstract: Patients with pectus excavatum (PE) often describe improvements in exercise stamina following corrective surgery. Studies have investigated the surgical effect on physiological parameters; still, no consensus has yet been reached. Therefore, the aim of this literature review was to describe the cardiac outcome after surgical correction, both at rest and during exercise. In February 2016, a detailed search of the databases PubMed, Medline, and EMBASE was performed. We assessed clinical studies that described ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…Secondly, with the large influx of patients, it was now possible to study cardiopulmonary function. Numerous studies have been performed since, demonstrating that there is significant cardiopulmonary dysfunction pre-operatively and significant improvement post-operatively (16)(17)(18). Research performed at The Children's Hospital of the Kings Daughters (CHKD) demonstrated a possible explanation for improved respiratory mechanics after pectus excavatum repair, using motion analysis (19).…”
mentioning
confidence: 99%
“…Secondly, with the large influx of patients, it was now possible to study cardiopulmonary function. Numerous studies have been performed since, demonstrating that there is significant cardiopulmonary dysfunction pre-operatively and significant improvement post-operatively (16)(17)(18). Research performed at The Children's Hospital of the Kings Daughters (CHKD) demonstrated a possible explanation for improved respiratory mechanics after pectus excavatum repair, using motion analysis (19).…”
mentioning
confidence: 99%
“…The improvement of maximum oxygen consumption in our study after surgical repair appears to be due to increase in stroke volume during exercise, and our results are similar to other published studies. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in exercise capacity is reported after insertion of a Nuss bar to repair PE; this has been shown to be related to improved ventricular filling as the heart is relieved of compression by the displaced sternum [810]. The impact of PE upon respiratory mechanics is more controversial with inconsistent results of both static lung function and non invasive assessment of chest wall motion [4, 11].…”
Section: Discussionmentioning
confidence: 99%